Employability Appraisal Scale (EAS): Development and Validation in a Spanish Sample - Llinares-Insa, Lucía I.; González-Navarro, Pilar; Zacarés-González, Juan J.; Córdoba-Iñesta, Ana I. (Frontiers in Psychology, 2018)
Employability is an important issue in the labor context. Currently, the European Union presents employability as the path to full employment and active citizenship, and a strategy to reduce unemployment and poverty. This study develops and validates an Employability Appraisal Scale. Specifically, we propose a multidimensional employability scale that analyzes both individual indicators and personal circumstances from the Bioecological Model of Employability. The Employability Appraisal Scale (EAS) assesses personal and social dimensions of employability. It was developed and tested using data from 489 people from a very heterogeneous sample (precarious workers, professionals, prisoners, long-term unemployed, socially excluded, etc.). Results provide evidence for the multi-dimensional structure and validity of the EAS. This scale is a valid and reliable instrument to measure employability, and it provides criteria for interpreting scores. Finally, we present theoretical and practical implications of the EAS for social and labor integration, job transition, and career development. Our findings have positive implications for identifying effectiveness indicators in training programs, and they contribute to designing intervention policies to increase employability.